Niche Analysis of Competition among Music Streaming Services in Korea - Saehe Shin (International Telecommunications Society (ITS), 2024)
With the advancement of digital technology, the music industry has undergone significant changes, with music streaming services becoming the primary means of music consumption worldwide. In South Korea, native music streaming platforms like Melon and Bugs have long dominated the market. However, the recent rapid growth of global platforms such as YouTube Music has intensified the competition. This study focuses on adolescent users to analyze the competitive relationships among major music streaming platforms in this competitive environment. Four platforms—YouTube Music, Melon, Genie Music, and Flo—were selected for the study, and a survey was conducted with youth users aged 14 to 18. Based on niche theory, five fulfillment factors were defined: music diversity, recommendation services, additional services, price value, and ease of use. The competitiveness of each platform was analyzed based on these factors. Through this analysis, the study aims to provide strategic implications for South Korean music streaming platforms to achieve sustainable success in the face of global competition. By doing so, it aims to provide strategic insights for South Korean music streaming platforms to achieve sustainable success in competition with global platforms that are gradually increasing their market share.
Keywords: 330; music streaming; music streaming service; music streaming platform; niche analysis; Melon; Genie Music; FLO; YouTube Music